2010
DOI: 10.1021/bc9004798
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid-Conjugated Chitosan Nanoparticles Enhanced Protoporphyrin IX Accumulation in Colorectal Cancer Cells

Abstract: Folic acid can be covalently conjugated to chitosan molecules via its gamma-carboxyl moiety and thus retain a high affinity for colorectal cancer cells bearing folate receptor overexpression. Colorectal cancer is one of the leading causes of malignant death and often goes undetected with current colonoscopy practices. Improved methods of detecting dysplasia and tumors during colonoscopy will improve mortality. A folic acid conjugated chitosan nanoparticle as a suitable vehicle for carrying 5-aminolaevulinic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
158
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(166 citation statements)
references
References 33 publications
8
158
0
Order By: Relevance
“…Effective targeting with folate has been proven by using folate on the surface of many nanocarriers such as gold nanoparticles, liposomes or magnetic nanoparticles for the detection of cancer cells and the release of anticancer drugs. [57][58][59] All conjugates were able to release the drug in a pH-dependent manner with no role played by enzymes. The presence of a plasma enzyme does not accelerate the conversion of different compounds in dFdU which confirms previous studies showing that the protection of the amino group of gemcitabine prevents this.…”
Section: Peg-gemcitabinementioning
confidence: 99%
“…Effective targeting with folate has been proven by using folate on the surface of many nanocarriers such as gold nanoparticles, liposomes or magnetic nanoparticles for the detection of cancer cells and the release of anticancer drugs. [57][58][59] All conjugates were able to release the drug in a pH-dependent manner with no role played by enzymes. The presence of a plasma enzyme does not accelerate the conversion of different compounds in dFdU which confirms previous studies showing that the protection of the amino group of gemcitabine prevents this.…”
Section: Peg-gemcitabinementioning
confidence: 99%
“…The same authors ascribed the broad and complex band at 1696 cm -1 to the stretching of different -C=O groups, and the band at 1607 cm -1 to the bending of -NH groups. In contrast, Yang et al [23] assigned both the band at 1607 cm -1 and the band at 1449 cm -1 to the stretching of aromatic C=C bonds. Vora et al [24] assigned the bands between 2860 and 2960 cm -1 to the symmetric and antisymmetric stretching of C-H bonds.…”
Section: Resultsmentioning
confidence: 92%
“…35 Furthermore, other researchers have reported that chitosan hydrogels or folic acid-conjugated chitosan can be an efficient carrier for delivering 5-ALA to tumor cells. 37,38 Yang et al also observed time-dependent accumulation of pPIX in the tumor cells and pPIX accumulation was highest at 112 hours of incubation. Our results revealed that PEG-Chito-5-ALA nanoparticles also induce enhanced phototoxicity against CT26 colon cancer cells and then accelerate the apoptosis or necrosis of the cells, as shown in Figure 8.…”
Section: Discussionmentioning
confidence: 93%
“…1,2,6,10 To overcome these problems, chemical modification of 5-ALA, 5-ALA-incorporated nanocolloid, patch-based delivery system, or liposomal carriers were tried, in order to improve delivery of 5-ALA. 14,15,18,19 Chitosan has been extensively investigated as a geneor drug-delivery carrier. [25][26][27][28][33][34][35] In particular, chitosan is known to enhance mucosal transport or delivery of bioactive agents. 34,35 Therefore, chitosan is regarded as a promising vehicle for transmucosal or oral delivery of drugs.…”
Section: Discussionmentioning
confidence: 99%